Evolving Sounds - KEEGAN, BRIAN (Trinity College Dublin. School of Creative Arts. Discipline of Music, 2018)
Abstract This work concerns the role of musical time and space in relation to the body of compositions that form part of this research. Although these two areas are immense, they are nonetheless unavoidable in music composition. The physics of the last one hundred years confirms, the movement of time is relative. This is no less the case in music. There is clock time which marks the passage of our existence but there is also another time that is both complex and liberating. The latter time can seem to be stretched or compressed or completely static. These are the parameters that can be experimented upon in music composition. The contents of successive slices of time are also fruitful areas for experimentation. Space can be filled so that it seems dense and massive. Alternatively, it may be filled very delicately so that it is almost transparent. When sounds become thin enough, they give way to silence. The compositions that make up this research explore various aspects of time and space as outlined above. For example, in ?Suspiramus?, the silences, marked by fermatas of varying length, have the same status as the audible sound. Just as with breathing, in this composition, the silent rested part is as important as the noisy in-out movement. The research presented here explores the connection between the static work of art, visible in an instant and music which unfolds over time. It looks at the influence a number of art works have had on the composition of these pieces. For example, the role of dynamism in painting and its influence on the buzzing snare drum rolls on which Mj?llnir is built. As the representation of time and space in compositions becomes more complex and problematic, issues around the notation of these are examined.
APPROVED
Keywords: Music; Composition; Space; Time; Evolving Sounds